The Influencing Factors of Artificial Intelligence Improving Chengdu Consumer Satisfaction in Apparel Industry - Yanqing Zhang (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The apparel industry in Chengdu is transforming significantly due to integrating artificial intelligence (AI) technologies. This evolution aims to enhance consumer satisfaction by providing personalized shopping experiences, improving inventory management, and streamlining the supply chain. AI-driven algorithms analyze consumer behavior and preferences, allowing retailers to create tailored recommendations that align with individual tastes. Additionally, AI tools enable efficient inventory management by predicting trends and consumer demand, which helps reduce instances of overstock and stockouts. This optimization improves operational efficiency and ensures customers can find their desired products when visiting stores or online. This study was conducted through an online questionnaire distributed to 376 Chengdu participants to measure their attitudes toward AI improvement in the apparel industry. The findings underscore that innovative technology, perceived information quality, and perceived customization correlate with consumer satisfaction in AI experience improvement.